Dynamic analysis of anti-dip bedding rock slopes reinforced by pre-stressed cables using discrete element method. (1st September 2021) - Zheng, Yun; Wang, Runqing; Chen, Congxin; Sun, Chaoyi; Ren, Zhanghao; Zhang, Wei
Abstract: Pre-stressed cables were found to be a viable approach of reinforcing anti-dip bedding rock slopes (ABRSs) in the Wenchuan earthquake. However, the dynamic response law and failure mechanism of reinforced ABRSs are still unclear, which was studied using the Universal Distinct Element Code (UDEC) method in this work. A numerical model of a typical ABRS was first built up using UDEC. Then, a comparison of the dynamic response of reinforced and unreinforced ABRSs was carried out. Moreover, a systematic parameter study was performed to investigate the effect of cable inclination, cable spacing, and pre-stressed force on the reinforcement effect. The results show that pre-stressed cables can be very effective in controlling the deformation and improving the dynamic stability of ABRSs subjected to dynamic loading. For both unreinforced and reinforced ABRSs, a remarkable acceleration amplification occurs on the surface of the slope from half of the slope height upwards. A small cable inclination and a high pre-stressed force are recommended in the seismic reinforcement design of ABRSs. The results of this work could guide the design of reinforcement of ABRS in earthquake-prone areas.